Vector Autoregressive Modeling of Some Nigeria Inflation Factors - D, Idi; J, David I. (Darul Yasin Al Sys, 2024)
This study investigates the modeling of some macroeconomic variables in Nigerian using multivariate monthly time series data from January 2010 to December 2019. The study examined two inflation factors which include money supply (MS) and exchange rate (ER) which are of great importance in determining inflationary effect in any economy. If MS is greater than ER then it can be said that the economy is experiencing rise in inflation and vice versa. Based on the analysis of implementing a vector autoregressive model to the data at stationarity using the Augmented Dickey–Fuller (ADF) test, Inflation rate (IR) was found to be significant only at lag 2 of IR. However, MS was found to be significant at lag 1 of ER and ER was significant at lag 1 and lag 2 of ER. The impulse response function plots clearly showed an unstable IR on MS and ER but at the later end of the periods, Nigeria IR tends towards a positive stability on MS and ER, respectively.